Treatment of Advanced Hormone Receptor-Positive (HR+) HER2-negative Breast Cancer - Ditsch, Nina; Schmidt, Marcus (Geburtshilfe und Frauenheilkunde, 2019)
The article gives an overview of current treatment options for metastatic hormone receptor-positive and HER2-negative breast cancer. The focus is on combined therapies, e.g., with CDK4/6 inhibition compared with purely endocrine-based therapies in the pre- and postmenopause, presenting the latest study results. The addition of a CDK4/6 inhibitor to endocrine-based therapy with an aromatase inhibitor or fulvestrant leads to a marked improvement in progression-free survival and is independently beneficial whether palbociclib, ribociclib or abemaciclib is involved. The particular clinical status of inhibition of cyclin-dependent kinases argues for its use in the first-line treatment of women with metastatic, hormone receptor-positive and HER2-negative breast cancer compared with the available purely endocrine-based therapies.
Keywords: breast cancer; metastasis; hormone receptor-positive; HER2-negative; CDK4/6 inhibitor